2020
DOI: 10.1111/tid.13400
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Torque Teno Virus in hemodialysis and renal transplant patients in Australia: A cross‐sectional study

Abstract: Renal transplantation is the most common and successful type of solid organ transplantation and revolutionalizes the lives of thousands of people every year. Unfortunately, several challenges remain in this field, the key one being the risks of immunosuppressive therapy. A key unmet need is a method of precise and individualized monitoring to measure the actual functional status of a patient's immune system at any given time. Several assays have been proposed to fill this need, but none have entered routine cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…Notably, only TTV was positive in all three types of samples with nucleic acid reads ≥100 and relative abundance ≥10%, which was completely unexpected. The detection rate of the TTV was 66.00% in all samples, and 100.00% in blood samples, which is consistent with the findings of previous studies ( 33 , 34 , 39 ). In addition to the detection in these types of samples, detection of the TTV in cerebrospinal fluid has also been reported ( 40 ), suggesting that the TTV may be widely present in human body fluids and may be particularly evident in immunosuppressed population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, only TTV was positive in all three types of samples with nucleic acid reads ≥100 and relative abundance ≥10%, which was completely unexpected. The detection rate of the TTV was 66.00% in all samples, and 100.00% in blood samples, which is consistent with the findings of previous studies ( 33 , 34 , 39 ). In addition to the detection in these types of samples, detection of the TTV in cerebrospinal fluid has also been reported ( 40 ), suggesting that the TTV may be widely present in human body fluids and may be particularly evident in immunosuppressed population.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the detection in these types of samples, detection of the TTV in cerebrospinal fluid has also been reported ( 40 ), suggesting that the TTV may be widely present in human body fluids and may be particularly evident in immunosuppressed population. An Australian cross-sectional study noted that TTV was detectable in the plasma of 93% of KTRs, suggesting that TTV may be a novel marker for immunosuppressive therapy for KTRs ( 39 ). Another study has also identified TTV as a predictor of the level of immunosuppression and infection after solid organ transplantation ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…40 The association observed in various studies between male gender and higher viremia rates and TTV loads 32,34,41 has been linked to the potential role of sexual transmission or to the differential impact of sex steroid hormones on the host's immune system. 42 In addition, higher rates are found in patients with underlying conditions, including hypertension and diabetes mellitus, 33 human immunodeficiency virus (HIV), 43 chronic hepatitis B or C virus infection, 37,44 rheumatoid arthritis, 45 chronic renal disease on hemodialysis, [46][47][48] systemic erythematosus lupus, 49 or cancer. 33,50 Haloschan et al…”
Section: Epidemiology In the Non-transplant Populationmentioning
confidence: 99%
“…58,59 Frye et al observed an unexpectedly high baseline rate of TTV-negative patients in their LuT cohort (67.6%), which was explained on the grounds of differences in PCR sensitivity. 60 To put these figures in context, the presence of detectable TTV viremia in non-transplant patients with chronic conditions leading to end-stage organ failure is estimated at 41.7% 46 to 80% 47 for those on hemodialysis, 95% for those with chronic obstructive pulmonary disease, 61,62 and as high as 100% for those with idiopathic pulmonary fibrosis. 63,64 Of note, these figures are higher as compared to healthy individuals, 32,65 supporting the hypothesis that TTV replication is enhanced not only by impaired immune competence but also by persistent low-grade inflammatory status.…”
Section: Baseline Prevalence and Post-transplant Kineticsmentioning
confidence: 99%
“…Thirty‐three records remained after removing 20 duplicates. After reviewing the title, abstract, full‐text, and excluding the articles that failed to meet the included criteria, 11 articles 18,19,23,32–34,42–46 were included for meta‐analysis (Table 1), including 7 prospective cohorts studies, 18,19,32–34,42,46 2 cross‐sectional studies, 23,43 1 retrospective cohort study, 45 and 1 case series report 44 . Most plasma TTV DNA load was quantified at post‐months 1, 3, 6, and 12 by TaqMan real‐time polymerase chain reaction (PCR).…”
Section: Resultsmentioning
confidence: 99%